2017
DOI: 10.1002/app.45979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano‐silica on gas permeation properties of polyether‐based polyurethane membrane in the presence of esterified canola oil diol as a nucleation agent for hard segments

Abstract: In this research esterified canola oil diol (COD) was used to synthesize a green thermoplastic polyurethane. The mixture of synthesized COD as a polyester and polytetramethylene‐glycol as a polyether with different molar ratios were used to synthesize a thermoplastic polyurethane. Membranes were prepared by solution casting technique and nano‐silica particles were used to improve their gas separation performance. The effects of COD segments on phase separation and thermal properties of blocky segments of polyu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Although a great variety of membrane materials have already been investigated for gas separation applications, polymers are still being exclusively used in large scale or in industries [1]. Polyurethane membranes are reported in the literature with the addition of some substances, such as salts, to improve selectivity [2][3][4][5][6]. However, the major challenge to implement this technology is cost reduction; thus, a proposal of a polyurethane membrane without the addition of any other components could be economically more feasible and more sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…Although a great variety of membrane materials have already been investigated for gas separation applications, polymers are still being exclusively used in large scale or in industries [1]. Polyurethane membranes are reported in the literature with the addition of some substances, such as salts, to improve selectivity [2][3][4][5][6]. However, the major challenge to implement this technology is cost reduction; thus, a proposal of a polyurethane membrane without the addition of any other components could be economically more feasible and more sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have consistently shown that traditional separation processes, such as distillation and chemical adsorption, lack environmental conservation processes. In recent years, the application of polymer membrane materials in gas separation has become a reliable alternative because these materials consume low energy, are highly efficient, and present little harm to the environment . Hence, the membrane‐based gas‐separation method, which is more environmentally friendly, plays a key role in scientific and industrial processes …”
Section: Introductionmentioning
confidence: 99%